The effect of optimal temperature management, reliable infrastructure, technology and digitalization, proper packaging, HR competence on cold chain logistics efficiency - Soekirman, Atong; Simarmata, Juliater; Saribanon, Euis; Sihombing, Sarinah (Edelweiss Applied Science and Technology, 2025)
The purpose of this literature research is expected to help hypotheses for future authors in determining research related to logistics management. The research article on the effect of optimal temperature management, reliable infrastructure, technology and digitalization, proper packaging, and human resource competence on cold chain logistics efficiency is a scientific literature article within the scope of logistics management. The approach used in this literature review research is descriptive qualitative. Data collection techniques involve literature studies or conducting literature reviews of relevant previous articles. The data used in this research is secondary data, sourced from academic online media such as Thomson Reuters Journals, Sage, Springer, Taylor & Francis, Scopus, Emerald, Elsevier, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar, and digital reference books. In previous studies, one relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Optimal Temperature Management affects Cold Chain Logistics Efficiency; 2) Reliable Infrastructure affects Cold Chain Logistics Efficiency; 3) Technology and Digitalization affect Cold Chain Logistics Efficiency; 4) Proper Packaging affects the Efficiency of Cold Chain Logistics; and 5) HR Competence affects the Efficiency of Cold Chain Logistics.